Karakteristik Selai Cokelat Dengan Perbandingan Bubuk Kakao (Theobroma Cacao L.) Dan Minyak Kedelai (Glyncine Max Oil) - I Gusti Ayu Adindari Suarasmara; I Dewa Gde Mayun Permana; I Wayan Rai Widarta (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Abstract If chocolate jam was processed using cocoa butter, it resulted low spreadability. Therefore, it was necessary to investigate the use of liquid oils such as soybean oil as an alternative. The aim of this research was to determine the effect of ratio of cocoa powder to soybean oil and identify the optimal ratio for the best characteristics of chocolate jam. This study used Completely Randomized Design (CRD) with six treatment of cocoa powder and soybean oil ratios, 64%:36%, 61%:39%, 58%:42%, 55%:45%, 52%:48%, and 48%:52%. Each treatment was repeated three times, resulting 18 experimental. Data were analyzed using Analysis of Variance (ANOVA), and if a significant effect was observed (P<0,05), Duncan’s Multiple Range Test (DMRT) was conducted. Sensory evaluation were analyzed using Principal Component Analysis (PCA). The research results showed that the ratio of cocoa powder to soybean oil had a significant effect on the characteristics of the chocolate spread. Soybean oil improved the texture quality and spreadability of the chocolate spread without damaging the flavor and sensory acceptance. Chocolate jam with best characteristics was obtained from the formulation containing 55% cocoa powder and 45% soybean oil which corresponds to treatment P4, with characteristics of moisture content 16.79%, ash content 1.58%, fat content 25.26%, hardness 1,36 N, cohesiveness 0,31, adhesiveness 6,36 Nmm and the treatment received